THE SELF-MEANING BUILT BY JOURNALIST IN BANTEN PROVINCE IN SPREADING HATE SPEECH IN THE PRESIDENTIAL ELECTION 2019 - Liza Diniarizky Putri; Annisarizki Annisarizki; Dicky Andika (ASPIKOM Jabodetabek Region, 2020)
The current mass media industry is not the only sovereign of the source of informations. Based on technological advancements, social media exists as a blurring medium for space and time constraints in disseminating and exchanging information, but the minimal control mechanism causes content on social media is not only be positive, but also can be negative such as the spread of hate speech. Hate speech also enlivening journalist's Facebook accounts in Banten, especially during the 2019 Presidential Election campaign which tends to be a